2013
DOI: 10.1159/000355671
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antipruritic Effects of Topical Pimecrolimus in Non-Atopic Prurigo Nodularis: Results of a Randomized, Hydrocortisone-Controlled, Double-Blind Phase II Trial

Abstract: Background: In the treatment of atopic dermatitis, pimecrolimus has high antipruritic effects. Objective: To investigate the efficacy of 1% pimecrolimus cream in comparison to 1% hydrocortisone cream in non-atopic prurigo nodularis (PN). Methods: A randomized, controlled, double-blind study with intraindividual randomization was done in 30 patients (17 females, 13 males; mean age 58.5 years) with PN. Results: Pruritus intensity decreased significantly (p < 0.001) on both treated sides as early as after 10 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 23 publications
1
40
0
1
Order By: Relevance
“…Also, no previous study investigated DLQI in a large number of PN patients except in single trials. For example, Siepmann et al [27] used DLQI in a randomized controlled trial and demonstrated DLQI values >11 in all PN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, no previous study investigated DLQI in a large number of PN patients except in single trials. For example, Siepmann et al [27] used DLQI in a randomized controlled trial and demonstrated DLQI values >11 in all PN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Basis for the development of PAS were the earlier applied PRUNOSI and SSS scores . The PAS questionnaire version 0.9 consists of 7 items (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…However, none of these scales were validated or used in subsequent trials. So far, we used preliminary versions of a prurigo score (PRUNOSI, Scratch Symptom Score (SSS)) in two clinical studies (ClinicalTrials.gov: NCT00507832, German Register Clinical Trials: DRKS00005284) . PRUNOSI evaluated the type (papules, nodules, lichenification, excoriations and crusts) and percentage of lesions in affected body areas versus the whole body area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Habit reversal therapy for the itchscratch cycle may be helpful and can be administered by dermatology nurses trained in this therapy. Cryotherapy with liquid nitrogen helps reduce pruritus and flatten lesions.…”
Section: 3mentioning
confidence: 99%